Cellular stiffness and deformability - Mierke, Claudia (Physics of Cancer, Volume 1, 2018)
Cells interact with and thereby sense their microenvironments via their cell surfaces. Hence, cellular surfaces are crucial in basic cellular processes such as signaling, communication, adhesion, migration, sensing, transport, energy generation, embryonic and tissue development, cancer metastasis, and viral as well as bacterial infections. These highly complex and multi-facetted functions of cell membrane surfaces are driven by the structural assemblies or scaffolds and their dynamic assembly. It is crucial to reveal how these cellular molecules structurally assemble and how they alter their cellular interaction with other neighboring cells and their microenvironment. Every single process of the cell's membrane surface is driven by a complicated interaction based on chemical, biological and physical cues. The typical interactions at cell membrane surfaces are of hydrophobic, hydrophilic, electrostatic, van der Waals and hydrogen bonding nature. In order to reveal insights into these interactions, it is necessary to understand how a cell surface receptor recruits its ligand, how and where the ligand binds within the huge receptor, and by which molecular mechanism the ligand switches to the functional state of its targeted receptor. Moreover, we need to understand how cellular interactions can regulate the assembly and functional state of cell surface receptors. Hence, a conceptual understanding of cellular forces goes beyond the simple description of the sensing, transduction and response of cells to mechanical cues, instead the functional dependences need to be revealed and impaired in order to prove the concept.
CRIS-Team WoS Importer:2019-08-27